Application of bearing and distance trees to the identification of landmarks on the coast - Praczyk, Tomasz (Zielona Góra: Uniwersytet Zielonogórski)
The problem of continuous position availability is one of the most important issues connected with the human activity at sea. Because the availability of satellite navigational systems can be limited in some cases, e.g. during military operations, one has to consider additional methods of acquiring information about the ship`s position.
Keywords: ship`s positioning; landmark identification; bearing and distance tree